ANALISA PENERAPAN PEMBIYAAN MUDHARABAH DALAM MENINGKATKAN USAHA MIKRO KECIL MENENGAH (STUDI PADA BSI UIN STS JAMBI) - Tiara Risma; Maulana Yusuf (ICONS: Islamic Economics Journal, 2026)
This study analyzes the application of the Pengen mudharabah approach as an innovative strategy in improving the performance of Micro, Small, and Medium Enterprises (MSMEs). Pengen Mudharabah is a movement that prioritizes the spirit of change and creativity of the younger generation, believed to be able to encourage digital transformation, strengthening branding, and developing products that are adaptive to the market. The research method used is a qualitative study with a case study approach on several MSMEs that have implemented the principles of Mudharabah. The results of the study show that the application of Mudharabah values such as the courage to innovate, the use of digital technology, and crosssector collaboration can increase the competitiveness of MSMEs, expand market access, and encourage sustainable business growth. These findings recommend strengthening the role of the younger generation as agents of change in the national MSME ecosystem.